Usability evaluation of mobile devices user interface (Nexo Revista Científica, 2021)
Designs of mobile human-computer interaction (HCI) target to create interactive and familiar products that are simple and interested to use. The mobile devices such as smartphones or tablets are becoming more and more popular and may to some extent replace the desktop computer and laptop as the most prominent hardware for HCI. This article presents a technical background for this area, the survey of selected user interface (UI) usability principles of today’s mobile devices design and user’s interaction for evaluation purposes. The experiment conducted through a questionnaire having four elements related to usability, i.e. usefulness, ease of use, ease of learning, and satisfaction. Furthermore, the evaluation process performed using quantitative analysis to understand and investigate the participants’ responses based on the Likert scale. The results suggested that most of the participants show a high level of satisfaction towards mobile devices and its interface. The attained level of satisfaction for each element was recorded as 63% for usefulness, 71% for ease of learning, 78% for ease of use and 70% for satisfaction. The collected results can guide the developers and mobile companies to understand the satisfaction level of mobile users. It will also help them to enhance the design and user interface of mobile applications based on usability and flexibility.